Chloride Ion as Redox Mediator in Reducing Charge Overpotential of Aprotic Lithium‐Oxygen Batteries. Issue 1 (9th October 2020) - Zhang, Qi; Zhou, Yin; Dai, Wenrui; Cui, Xinhang; Lyu, Zhiyang; Hu, Zheng; Chen, Wei
Abstract: The aprotic lithium‐oxygen (Li−O2 ) battery with a high theoretical energy density has been considered as a promising candidate for next‐generation energy storage devices. However, the formation of insulating Li2 O2 products is a major obstacle for realizing the high energy efficiency and long cycle life. Here, we report a new Cl − /Cl3 − redox mediator to reduce the charge overpotential by a facile introduction of chloride ion (Cl − ) additives into the organic electrolyte. The redox mediator can effectively promote the formation of the LiOH discharge product, and facilitate efficient LiOH decomposition. Therefore, the cell with the Cl − additives possesses a significantly low charge overpotential of 0.29 V, an extended cycle life (up to 71 cycles) at a rate of 500 mA g −1 with a fixed capacity of 500 mAh g −1, and an enhanced rate capability. This study offers an effective approach to modulate discharge products from Li2 O2 to LiOH and provides new insights toward the role of redox mediators through the addition of Cl − in Li−O2 battery systems. Abstract : With or without you : An efficient aprotic Li−O2 battery cycling via the reversible formation and decomposition of discharge product LiOH by the addition of a chloride source is demonstrated. The dominate discharge product LiOH and the Cl − /Cl3 − redox mediator couple help achieve low charge overpotential (0.29 V), large discharge capacity of 8386 mAh g −1, excellent rate capability, and an excellent cycle life (up to 71 cycles) at 500 mA g −1 with a fixed capacity of 500 mAh g −1 .